2019
DOI: 10.1259/dmfr.20180393
|View full text |Cite
|
Sign up to set email alerts
|

An audit and service evaluation of the use of cone beam computed tomography (CBCT) in a paediatric dentistry department

Abstract: Objectives: CBCT exposes the paediatric patient to a higher X-ray dose and risk than normal dental radiographs. This study has two components: an audit and service evaluation. The audit aims to assess whether the use of CBCT in a Paediatric Dentistry department at a London hospital complies with European guidelines (SEDENTEXCT). The service evaluation aims to explore the influence of CBCT on treatment planning. Methods: Two 6 month audit cycles were completed, where CBCT requests were audited to check whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 6 publications
3
17
0
1
Order By: Relevance
“…This study supports the findings from a (single unit) similar service evaluation by Mizban et al ( 2019 ) who found that CBCT can significantly change the diagnoses and opinions in teeth with dental trauma and pathology associated with developmental anomalies. The impact that CBCT has on treatment planning also supports a statement by IATD ( 2012 ) on CBCT: it provides improved visualisation of traumatic dental injuries, particularly root fractures and lateral luxation injuries, monitoring of healing, and complications.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study supports the findings from a (single unit) similar service evaluation by Mizban et al ( 2019 ) who found that CBCT can significantly change the diagnoses and opinions in teeth with dental trauma and pathology associated with developmental anomalies. The impact that CBCT has on treatment planning also supports a statement by IATD ( 2012 ) on CBCT: it provides improved visualisation of traumatic dental injuries, particularly root fractures and lateral luxation injuries, monitoring of healing, and complications.…”
Section: Discussionsupporting
confidence: 91%
“…The most common indication for requesting a CBCT was to investigate the local developing dentition and when examined within age group categories, this remained consistent in all age groups 4–6, 7–12 and 13–16 years (50%, 73%, 62%) and was succinct with the findings from other studies (Barba et al 2018 ; Mizban et al 2019 ). The divison of clinical indications was further divided into different groups for these studies whereby in the present study assessment of the localised developing dentiton group included teeth with root resoption unrelated to dental trauma, bony pathology, supernumeries and unerupted teeth.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In 73.5% of records (147/200), investigations required following the occurrence of events were reported, with the most frequently applied instrumental investigations (42.2% of cases). These assessments, as easily understood, determine an important investment of human and economic resources, precluding the possibility of being able to allocate them elsewhere [ 20 ].…”
Section: Discussionmentioning
confidence: 99%